Case Report: Papillary Thyroid Cancer in a Patient with Celiac Disease and Thalassemia Trait - Afaf Albattah; Yahia Imam; Ahmed Osman Saleh; Khalid Ahmed; Tarek Aboursheid; Samah Kohla; Shehab Mohamed (Case Reports in Oncology, 2020)
Thyroid cancer is the most frequent endocrine neoplasm in the general population. Common risk factors include gender, radiation exposure, and genetic backgrounds. The association of papillary thyroid cancer and celiac disease has frequently been reported in the literature; however, the association of papillary thyroid cancer and thalassemia trait is rare. Likewise, the association of thalassemia major and celiac disease is also rare. We hereby report a unique case of papillary thyroid cancer in a patient with celiac disease and thalassemia trait.